Injustice and the Disappearance of Discretionary Detention under Trump: Detaining Low Risk Immigrants without Bond - Evans, Kate (2020)
This Report demonstrates that the Immigration and Customs Enforcement (ICE) violates legal requirements to provide immigrants with an individualized custody determination. Trump’s enforcement policies brought a surge of low-risk immigrants into ICE custody. The detention risk tool was supposed to train officers and strongly discourage them from detaining low-risk immigrants who posed no harm to society and were not a flight risk. Data received pursuant to FOIA show the opposite result. ICE has failed to perform the individualized assessment and restrict its use of civil detention to only those whose high levels of dangerousness and risk of flight justify their incarceration. The data show that officers have manipulated the risk tool by subjecting low-risk immigrants to blanket detention, which has come to define the no-release Trump immigration policy in the New York City area